EVALUASI IMPLEMENTASI PROGRAM SEKOLAH DASAR STANDAR NASIONAL (SDSN) DI SEKOLAH DASAR NEGERI KABUPATEN TEMANGGUNG - Eriyani, Eriyani; Sutriyono, Sutriyono (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to describe the design, installation, process and product implementation SDSN program at SDN 1 Ngadirejo Temanggung. This study is evaluative, by using a mixed methods Discrepancy models. The data collecting technique used interview, questionnaires, study documentation, and observation. The validity of the data was done by using triangulation. The results of the study were (a) the design stage in accordance with the guidelines organizing school national standards, (b) the installation phase there was a shortage of space (c) phase of the process has not been implemented to the maximum, competency standards there was a gap in the medium category that has not been able to achieve in the level district or higher. Content standards had gaps with low category, the ownership of the curriculum document by 80%. Standard processes had gaps with low category that teachers rarely did ICT-based learning. Standard teachers and education personnel had gaps medium category that educators were still many of internship teachers(Guru Wiyata Bhakti). Standard facilities and infrastructure has a gap with category-less school grounds and space for PBM. Management standards had gaps lower categories, namely activities carried out 70-89% of new schools, school community involvement in decision making policy and school programs of up to 70-80%. Standard finance was still a gap with the low category for schools to implement the program required additional costs of the public. Assessment standards had gaps with low category because of the level of student learning outcomes documentation was only implemented by 75-90%. (d) Product implementation of programs already met the standard mastery learning is at least 95% and 90% of graduates go on to a higher school. The standards have not been met is the UN values above the regional average and have achievements in regional, national and international.